2012
DOI: 10.1001/dmp.2012.13
|View full text |Cite
|
Sign up to set email alerts
|

ILI-Related School Dismissal Monitoring System: An Overview and Assessment

Abstract: ABSTRACTObjective: This report provides an overview and assessment of the School Dismissal Monitoring System (SDMS) that was developed by the Centers for Disease Control and Prevention (CDC) and the US Department of Education (ED) to monitor influenza-like illness (ILI)-related school dismissals during the 2009-2010 school year in the United States.Methods: SDMS was developed with considerable consultation with CDC'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…During the 2009 H1N1 influenza pandemic, 1947 schools closed between August 3, 2009 and December 18, 2009, at least in part, due to ILI [31]. These closures affected 623 616 students and 40 521 teachers, and a total of 1 565 321 student-days of school were lost [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the 2009 H1N1 influenza pandemic, 1947 schools closed between August 3, 2009 and December 18, 2009, at least in part, due to ILI [31]. These closures affected 623 616 students and 40 521 teachers, and a total of 1 565 321 student-days of school were lost [31].…”
Section: Discussionmentioning
confidence: 99%
“…During the 2009 H1N1 influenza pandemic, 1947 schools closed between August 3, 2009 and December 18, 2009, at least in part, due to ILI [31]. These closures affected 623 616 students and 40 521 teachers, and a total of 1 565 321 student-days of school were lost [31]. Therefore, it is important to recognize that despite the lack of effect on slowing or reducing influenza/ILI transmission in communities, reactive school closures will most certainly cause difficulties to families.…”
Section: Discussionmentioning
confidence: 99%
“…During August–December 2009, communities in 46 U.S. states implemented 812 dismissal events (i.e., a single school dismissal or dismissal of all schools in a district), affecting 1,947 schools with approximately 623,616 students and 40,521 teachers ( 15 ). The 1,947 schools included 639 urban and 1,250 rural schools, representing 0.7% and 3.3% of all urban and rural schools, respectively, in the United States.…”
mentioning
confidence: 99%
“…During the 2009 pandemic, surveillance for pandemic-related school closures found that 81% of USCs resulted in <4 missed school days [9] . This differs from the pattern seen with respiratory illness-related closures in this study, which found that 94% of illness-related closures resulted in <4 missed school days.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these preemptive closures, school closures may be implemented reactively due to high levels of student and staff absenteeism related with widespread influenza transmission, as previously reported during local epidemics of seasonal influenza [5] , [6] and during influenza pandemics [7] , [8] . During the second wave of the influenza A(H1N1)pdm09 pandemic in the United States, which coincided with the start of the 2009–2010 school year, 812 school closure events were reported to a national surveillance system developed to monitor pandemic-related closure events from direct reports, state monitoring systems, and media scans and online searches [9] . This surveillance system provided important situational awareness with regard to pandemic-related school dismissals, including the geographic distribution, the number of school days missed, and the number of students affected by dismissal events.…”
Section: Introductionmentioning
confidence: 99%